Epistemologi Nilai dalam Islam dan Dinamikanya dalam Khazanah Intelektual Islam Klasik - Muhammad Zainal Abidin; Yulia Hafizah (Direktorat Pondok Pesntren Universitas Islam Indonesia, 2020)
This article departs from the view that the construction of values /morals / ihsan in Islam cannot be separated from the construction offaith (akidah) and Islam (worship). Similar to the relationshipbetween ontology (wujud), epistemology (ma'rifah), and axiology(qimah). The classical Islamic tradition is very rich with thediscussion on the epistemology of value, and this needs to beaddressed when issues of faith, worship, and values becomeproblematic and are seen as dichotomous in moslem society. Theresults of the study: First, the epistemology of values in the intellectualrealm of Islam can be grouped into two main schools, namely: 1) Therational school with 'aql as a source of value and has the ability toknow good and bad, even to know Allah Swt. Also known as objectiveethics; 2) Traditional schools, with revelation or inspiration / intuitionas the basis of values. It is also called subjective ethics, because thescope of its application is in certain areas, namely the believers, whobelieve in the truth of the revelation. Second, the issue of values ormorals is closely related to knowledge of the ins and outs of the soulas is the opinion of rationalists (Muslim philosophers), but theexperience dimension also plays an important role as the opinion oftraditionalists / intuitionists. Third, the dichotomous view of thesource of value makes it very possible for the birth of disintegrationin the main pillars of Islam, namely: Iman, Islam, and Ihsan.